Startup, scaleup, screwup : 42 tools to accelerate lean & agile business growth - Appelo, Jurgen, 1969- (John Wiley & Sons, Inc., 2019)
Real-world tools to build your venture, grow your business, and avoid mistakes Startup, Scaleup, Screwup is an expert guide for emerging and established businesses to accelerate growth, facilitate scalability, and keep pace with the rapidly changing economic landscape. The contemporary marketplace is more dynamic than ever before-increased global competition, the impact of digital transformation, and disruptive innovation factors require businesses to implement agile management and business strategies to compete and thrive. This indispensable book provides business leaders and entrepreneurs the tools and guidance to meet growth and scalability challenges head on. Equal parts motivation and practical application, this book answers the questions every business leader asks from the startup ventures to established companies. Covering topics including funding options, employee hiring, product-market validation, remote team management, agile scaling, and the business lifecycle, this essential resource provides a solid approach to grow at the right pace and stay lean. This book will enable you to: -Apply 42 effective tools to sustain and accelerate your business growth -Avoid the mistakes and pitfalls associated with rapid business growth or organizational change -Develop a clear growth plan to integrate into your overall business model -Structure your business for rapid scaling and efficient management Startup, Scaleup, Screwup: 42 Tools to Accelerate Lean & Agile Business Growth is a must-read for entrepreneurs, founders, managers, and senior executives. Author Jurgen Appelo shares his wisdom on the creative economy, agile management, innovation marketing, and organizational change to provide a comprehensive guide to business growth. Practical methods and expert advice make this book an essential addition to any business professional's library.